Preaching in Place: Reflections on the Sermons of Oscar Romero, Dislocated Pulpits, and the Dangers of an Incarnate Word (Homiletic, 2023)
Preaching becomes true preaching when it is grounded in real place. In real place the pulpit becomes a cross. Among those who have given their voice to preach such a located gospel is Oscar Romero (1917–1980), whose pulpit became a cross when he chose to preach a word not abstracted from his place, but that touched the wounds and sins of his own people. This paper highlights excerpts of Romero’s sermons and commends this preacher as a guide in imagining what “preaching in place” might look like today.